Analysis of Vision and Mission Dimensions Benchmark Standards Management of Catholic Education Against Improving School Quality - Dionisius Sihombing; Kisno Kisno (Jurnal Pendidikan Edutama, 2024)
The results will be used as a basis for reflection when creating the most recent education management policies, which will support efforts to preserve education through high-quality management of education. In accordance with the guidelines set forth by the Education Commission of the Indonesian Bishops' Conference, four benchmark standards from 13 Catholic education standards and benchmarks and four assessment dimensions are taken into consideration when determining the vision and mission dimensions. This kind of study is known as explanatory study. With a research population of 77 school units, data was gathered using a qualitative and quantitative approach. Five respondents from each of the school representatives made up the total of 385 respondents, which included principals, teachers, and staff members as well as eight supporting respondents who were parish priests, student parents, alumni, and alumni parents, as well as education observers. The study's findings showed that the benchmark standards' influence on raising school quality in the vision and mission domains of education management was 2.29, or in the good category (B). This indicates that the people who designed and implemented school instruction paid close attention to the original idea of using Catholic schools to spread Christian principles across the church. The school has done a good job of preserving its identity as a Christian school. To achieve the goal of becoming a top-notch institution, however, changes must be made to maximize this initial orientation.